Integrasi Proses Elektrokimia dan Adsorpsi Karbon Aktif untuk Pengolahan Lindi Tempat Pemrosesan Akhir Sampah - Muhsinun Muhsinun; Lalu Auliya Akraboe Littaqwa (Journal of Science and Technology: Alpha, 2026)
This study evaluated the performance of an integrated electrochemical and activated carbon adsorption process for the treatment of landfill leachate. The initial leachate characteristics showed a COD of 4,850 mg/L, color intensity of 6,200 Pt Co, and ammonia concentration of 780 mg/L, with a low BOD/COD ratio indicating poor biodegradability. The electrochemical process operated at an optimum current density of 20 mA/cm² achieved 46.3 percent COD removal and 62.5 percent color reduction within 120 minutes, with an energy consumption of 18.4 kWh/kg COD removed. Standalone adsorption using 20 g/L of activated carbon reduced COD by 38.7 percent and color by 71.2 percent within 150 minutes; however, adsorption capacity declined by 35 percent after two cycles without regeneration. The integrated system operated at pH 6, current density of 20 mA/cm², and 120 minutes hydraulic retention time achieved 78.9 percent COD removal, 91.4 percent color removal, and 64.8 percent ammonia reduction. The specific energy consumption decreased to 12.6 kWh/kg COD removed, demonstrating improved energy efficiency compared to the electrochemical process alone. In situ electrochemical regeneration conducted for 30 minutes at 30 mA/cm² restored up to 87 percent of the initial adsorption capacity after three operational cycles. These results confirm a significant synergistic effect between electrochemical oxidation and activated carbon adsorption, leading to enhanced treatment efficiency and operational stability for complex landfill leachate.